(untitled) (Philologia, 2021)
Sebia and the USA in the late 19th and at the beginning of the 20th centuries. Of all the literary genres, the story is said to have developed particularly in this period. The dialects and speech patterns of the common people were used in both Serbian and American literature. This paper summarizes the writings about Bret Harte, written in the period beginning in 1878 and ending in 1961. It can be concluded that he gained in popularity in the Serbian-speaking region at the end of the 19th century, between the two world wars, and after the Second World War. Harte won this popularity because his stories were drawn from events that really happened and he used a dialect to make his stories more interesting. The decline of his popularity started in the sixties with the rise of cynicism in the world. People lost the ability and naivety to believe in Harte’s optimism and opinion that even the most notorious criminal has a heart of gold.